Foot Motion Measurement for Home based Rehabilitation Using Distributed Wearable Sensor - WANG, ZHELONG; Qiu, Sen (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
This paper presents a wearable sensors based foot motion measurement method for rehabilitation applications. Two commercial wearable sensors were adopted with three measurement units fixed on feet. Quaternions were employed to represent three-dimensional orientation and an proportional-integral-filter (PIF) algorithm was used to calculate the quaternion derivative. Foot position and orientation were estimated and the effectiveness of the proposed method was validated on healthy subjects. Experimental results demonstrated that the proposed method is capable of providing consistent tracking of human foot without significant drift, with less than 0.5% position error, which matches that of Kalman based methods. The aim of this work is to allow therapists to make use of the biofeedback information to create biofeedback rehabilitation protocols, which can be used to monitor and evaluate rehabilitation progresses by the performance of patients doing prescribe corrective body movement and gesture. Moreover, this method could be applied to other cyclical activity monitoring.
Keywords: body sensor network; inertial sensors; motion measurement; rehabilitation